Codeine induces increased resistance at the esophagogastric junction but has no effect on motility and bolus flow in the pharynx and upper esophageal sphincter in healthy volunteers: A randomized, double‐blind, placebo‐controlled, cross‐over trial. Issue 5 (24th November 2020) - Geeraerts, Annelies; Geysen, Hannelore; Ballet, Lisa; Hofmans, Claudia; Clevers, Egbert; Omari, Taher; Manolakis, Anastassios C.; Mols, Raf; Augustijns, Patrick; Vanuytsel, Tim; Rommel, Nathalie; Tack, Jan; et al.
Abstract: Background: Chronic opioid use can induce esophageal dysfunction with symptoms resembling achalasia and a manometric pattern of esophagogastric junction—outflow obstruction (EGJ‐OO). However, the effect of opioids in acute setting on pharyngeal function and esophageal body contractility has not been investigated. Methods: After positioning the high‐resolution impedance manometry (HRiM) catheter, codeine (60 mg) or placebo (glucose syrup) was infused intragastrically. Forty‐five minutes post‐infusion, participants received liquid, semi‐solid, and solid boluses to assess esophageal and pharyngeal function. HRiM analysis was performed adhering to the Chicago classification v3.0. (CC v3.0). Pressure flow analysis (PFA) for the esophageal body and the pharynx was performed using the SwallowGateway™ online platform. Key Results: Nineteen healthy volunteers (HV) [5 male; age 38.3] were included. After codeine administration, higher integrated relaxation pressure 4 s values resulted in significantly reduced deglutitive EGJ relaxation and distal latency was significantly shorter. Distal contractility was similar in both conditions. Bolus flow resistance at the EGJ and distention pressures increased significantly after codeine infusion. Based on CC v3.0, acute infusion of codeine induced EGJ‐OO in six HV ( p  = 0.0003 vs. placebo). Codeine administration induced no significant alterations in any of the pharyngeal PFA metrics. Conclusions & Inferences: In HV, acute administration of codeine increased bolus resistance at the EGJ secondary to induced incomplete EGJ relaxation leading to major motility disorders in a subset of subjects including EGJ‐OO. However, an acute single dose of codeine did not affect motility or bolus flow in pharynx and UES. ClinicalTrials.gov number, NCT03784105. Abstract : In HV, acute administration of codeine increased bolus resistance at the EGJ secondary to induced incomplete EGJ relaxation leading to major motility disorders in a subset of subjects including EGJ‐OO. A) Change (in absolute numbers) for esophageal motility disorders assessed by the Chicago classification v3.0 before and after codeine administration. B) HRiM read‐out from one healthy volunteer who developed an EGJ‐OO after acute codeine administration. 1) After placebo administration: IRP4 = 12 mmHg; DCI = 1473 mmHg*cm*s; DL = 7.4 s: normal 2) After one single maximum dose of codeine administration: IRP4 = 30 mmHg; DCI = 2006 mmHg*cm*s; DL = 7.1 s: EGJ‐OO (major motility disorder). Abbreviations: HRiM= high resolution impedance manometry; EGJ‐OO= esophagogastric junction – outflow obstruction; IRP4= integrated relaxation pressure 4 seconds; DCI= distal contractile integral; DL= distal latency.